Chapter 3
Initial Value Problems





3.2 An Initial Value Problem: A Cooling Body

3.2.3 Solving the Initial Value Problem Symbolically

Now that we have seen a graphical interpretation of the solution of the initial value problem, we'll find a symbolic representation. Our differential equation for temperature of the cooling body is not exactly like the problems considered in Chapter 2 because the rate of change is proportional to T - 21 , not to T . That observation is what suggests the proposed change of dependent variable to y = T - 21 . Now

d y d t = d d t ( T - 21 ) = d T d t .

Thus, by substituting y = T - 21 and d y d t = d T d t into the original differential equation, we get a differential equation for the new unknown function `y`:

d y d t = - k y .

Also, at t = 0 , T = 30 , so y = T - 21 = 9 , which gives us an initial condition for the unknown function `y`. Thus, the substitution y = T - 21 transforms the original initial value problem to a new initial value problem:

d y d t = - k y   with   y = 9  at  t = 0 .

We illustrate the transformation from `T` to `y` in Figures 1 and 2. Figure 1 shows a slope field for the original differential equation. In Figure 2 we show the effect of the change of dependent variable, y = T - 21 , which is to move the horizontal axis from T = 0 to the level of room temperature, T = 21 or y = 0 . None of the slopes change because, at each value of `t`, d y d t = d T d t . Notice that the point `text[(]0,9text[)]` in Figure 2 corresponds to the point `text[(]0,30text[)]` in Figure 1.

Figure 1   Slope field for d T d t = - k ( T - 21 ) Figure 2   Effect of substituting y = T - 21

Our new initial value problem,

d y d t = - k y ,   with   y = 9  at  t = 0

should look familiar: It's the natural growth equation — except our growth factor is negative. The problem has exactly the form we saw in Chapter 2,

d y d t = r y ,   with   y = y 0  at  t = 0

with r = - k . (In form, it is also the problem you studied in Activity 2, Activity 4, and Example 3 in the preceding section.) So the solution must have the form we saw in Chapter 2:

y = y 0 e r t .

That is

y = 9 e - k t .

Of course, `y` is not the quantity we wanted to know about — it was merely a computational convenience. But we can reverse the change of the dependent variable by substituting y = T - 21 and solving for `T`:

T = 21 + 9 e - k t .

Checkpoint 2Checkpoint 2

Go to Back One Page Go Forward One Page

Go to Contents for Chapter 3Contents for Chapter 3